Examining women's and men's ideal criteria before forming families. Issue 1 (2nd January 2022) - Manze, Meredith G.; Watnick, Dana; Besthoff, Catherine; Romero, Diana
ABSTRACT: In the United States, family formation decision-making is more complex than the predominant models that have been used to capture this phenomenon. Understanding the context in which a pregnancy occurs requires a more nuanced examination. In-depth interviews were conducted with 60 men and women, aged 18–35, who had children or were pregnant. Using grounded theory analysis, themes emerged that revealed participants' ideal criteria desired before pregnancy. We stratified by those who met and did not meet these criteria. Almost universally, participants shared ideal criteria: to graduate, gain financial stability, establish a relationship, and then become pregnant. Many participants did not accomplish these goals. Those who had not met their criteria had experienced traumatic childhoods and suffered economic concerns. For this group, having children prompted positive changes within their control, but financial stability remained limited. Efforts should focus on improving circumstances for all individuals to fulfil their criteria before pregnancy.